(untitled) (Research, Society and Development, 2023)
Objective: To analyze the results of scientific research on the influence of COVID-19 on college students, identifying the mental disorders acquired both during and after the pandemic and verifying the effects of professional psychological monitoring during this pandemic period, aiming at emotional, physical, and social well-being. Methodology: To carry out this research, an integrative review was carried out. The inclusion criteria established to select the articles were to have been published in the period 2019 to 2022; available in Portuguese, English and Spanish with full text. The survey of information was conducted in the SciElO; Google Academic; LILACS; PePSIC; MedLine databases; using Boolean AND or OR with the descriptors "impacts of the pandemic", "COVID-19", "students", "college students" and "mental health" to conduct the search. Results: Twenty articles were used to construct this study, in which it was possible to observe a high index of depression, anxiety, substance abuse and increased stress due to the pandemic. Final considerations: The damage that social isolation and remote classes caused to college students during and after the COVID-19 pandemic was perceptible. In the face of the pandemic scenario, students stood out as a vulnerable audience to the emergence of mental disorders, which allow the appearance of cognitive impairments, consequently affecting the development of learning. Therefore, it is evident that higher education institutions need to promote pedagogical and psychological actions that help and guide students in this stage of educational changes, in a way that ensures the maintenance of the psychosocial well-being of these students.